Enhancing Data Management: An Integrated Solution for Database Backup, Recovery, Conversion, and Encryption Capabilities. - Sutar, Siddharth; Jose, Kevin; Gaikwad, Vidya; Mishra, Vaishali; Wankhede, Disha; Karnik, Madhuri (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In today’s world, there is a growing need for a flexible solution that can handle the complexities of SQL and MongoDB databases while providing reliable backup, recovery, conversion, and data protection in the constantly changing world of data management. The creation of an integrated backup, recovery, and conversion tool with encryption and decryption capabilities is described in this work. This application offers platform support for SQL and MongoDB databases, scheduling, backups, point-in-time recovery, and secure storage to meet the urgent needs of businesses and data professionals. Additionally, it provides smooth data transformation and schema mapping during conversion. The solution integrates strong encryption algorithms for data protection at rest and in transit and permits secure decryption utilising encryption keys and strategies like symmetric and Caesar cyphers. This improves data security. Essentially, the goal of our suggested technology is to improve and streamline data management, making it an essential resource in the current data-driven environment.